MANAJEMEN PENGELOLAAN WAHANA REKREASI OLAHRAGA DI WISATA AGRO KAMPOENG KOPI BANARAN KABUPATEN SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the management of sport recreational vehicle at Agro Tourism Kampoeng Kopi Banaran Kabupaten Semarang 2013. The method used in this research is a qualitative method-fenomologic naturalistic approach in which the process of data collection in field is through-interview and observation methods.From the research, there is a management process that is done in this place which is carrying out the planning process (planning), (organizing), leadership (leading) and control (controlling). For the fourth run the process in the management of this resort is influenced by factors from outside and inside. Based on the result of this research concluded that the sight implementing management processes. Referring to these results, researchers may submit suggestions, namely: 1) For Agro Tourism manager Kampoeng Kopi Banaran Kabupaten Semarang to continue to evaluate management so that management will be better. 2) For employees and other workers in order to maximize service to the visitors so that visitors in the sights activities more comfortable and memorable. 3) To PT. PTPN IX (Persero) associated with the thbureaucracy.